Rejected! Cognitions of rejection and intergroup anxiety as mediators of the impact of cross-group friendships on prejudice. - Barlow, F; Louis, W; Hewstone, M (2009)
In a sample of White Australians (N=273), cross-group friendship with Aboriginal Australians was associated with reduced cognitions of rejection and intergroup anxiety, and these variables fully mediated the effect of cross-group friendship on conversational avoidance of sensitive intergroup topics, active avoidance of the outgroup, and old-fashioned prejudice. The novel mediator proposed here, cognitions of rejection, predicted intergroup anxiety, and also predicted the three outcome variables via intergroup anxiety. Over and above its indirect effects via anxiety, cognitions of rejection directly predicted both conversational and active avoidance, suggesting that whilst the cognitive and affective mediators are linked, they predict intergroup outcomes in different ways. The results demonstrate the beneficial impact of cross group friendship in reducing prejudice and avoidance by diminishing cognitions of rejection and intergroup anxiety. We also highlight that individuals without cross-group friends may perceive the outgroup as rejecting, feel anxious about cross-group interaction, and desire both conversational and physical avoidance of the outgroup.